A new genus of speleophriid copepod (Copepoda: Misophrioida) from a cenote in the Yucatan, Mexico with a phylogenetic analysis at the species level - Boxshall, Geoff A.; Zylinski, Sarah; Jaume, Damià; Iliffe, Thomas M.; Suárez-Morales, Eduardo (Zootaxa, 2014)
A new genus and species of speleophriid copepod, Mexicophria cenoticola gen. et sp. nov., is described based on material collected from a cenote in the Yucatan Peninsula of Mexico. It is characterised by relatively reduced fifth legs that are located adjacent to the ventral midline in both sexes, by the possession of a bulbous swelling on the first antennulary segment in both sexes, and by the reduced setation of the swimming legs. The presence of just one inner margin seta on the second endopodal segment of legs 2 to 4 is a unique feature for the family. A phylogenetic analysis places the new genus on a basal lineage of the family together with its sister taxon, Boxshallia Huys, 1988, from Lanzarote in the Canary Islands, and recovers the existing genera as monophyletic units. The zoogeography is discussed at local, regional, ocean basin and global scales.